Impact of multifarious design architectures of convolutional encoders on efficiency of O-IDMA at zero dispersion wavelength - Prakash, Ravi; Kumar Maurya, Ajay (International Journal of Engineering and Technology, 2019)
Optical interleave division multiple access is a protrusive, obvious and flashy technology used in modern era mobile and wireless systems. Inter-leavers play a major role for estimating the performance of OIDMA system. In present article tree and random inter-leavers are incorporated in OIDMA system one by one and their qualitative comparison has been evaluated. Low rate convolutional encoders having various design topologies by varying number of adders and memory elements are used in coding section. Due to multifarious design architecture of encoders hamming distance ( ) alters for each case. Those architectures which has maximum will produces minimum BER (bit error rate). In present paper that optimum architecture which produces minimum BER has been determined for both tree and random    inter-leaver cases.